A disproportionality analysis of adverse events caused by GnRHas from the FAERS and JADER databases - Zou, Shupeng; Ouyang, Mengling; Zhao, Yazheng; Cheng, Qian; Shi, Xuan; Sun, Minghui (Frontiers in Pharmacology, 2024)
Background Gonadotrophin releasing hormone analogues (GnRHas) play a significant role in addressing gynecological diseases, central precocious puberty, and cancer. However, ensuring the safety of GnRHas in real-world applications requires continuous vigilance. In light of this, we undertook a disproportionality analysis focused on adverse events (AEs) associated with GnRHas, using data from both the FDA Adverse Event Reporting System (FAERS) and the Japanese Adverse Drug Event Report (JADER). We evaluated GnRHas-associated adverse events (AEs) and characterized the clinical priority of each GnRHa from the different databases.In the disproportionality analysis, we applied two adjusted algorithms to identify signals related to GnRHas in the FAERS and JADER databases from 2004 to 2023. Additionally, we utilized the Statistical Analysis System (SAS, 9.4) to examine potential and high-aROR (adjusted Reporting Odds Ratio) signals associated with GnRHas. We performed the clinical priority assessing for suspicious PTs and an analysis of serious/non-serious outcomes. We also gathered information on the onset times of adverse events (AEs) linked to GnRHas from both databases.From January 2004 to September 2023, the FAERS and JADER databases recorded a total of 50,360,413 and 1,440,200 adverse events (AEs), respectively. Employing two algorithms, suspicious preferred terms (PTs) related to leuprolide (Leu) with 562 potential PTs (44 unlisted in specifications), followed by goserelin (Gos) with 189 PTs (28 unlisted), triptorelin (Tri) with 172 PTs (28 unlisted), and Leu-JADER with 85 PTs (10 unlisted). At the same PTs level, differences in GnRHas between the two databases were observed, such as cardiac failure, diabetes mellitus, liver disorder, dementia, suicidal ideation, interstitial lung disease, urinary disorders, hypertensive crisis, and others. In an analysis of serious vs. nonserious outcomes, 77 PTs of Leu were more likely to be reported as serious AEs with p < 0.05 (such as hot flush, fatigue, dysuria, depression, and so on), followed by Tri (18 PTs) and Gos (7 PTs). Based on the clinical priority score,